Redox‐Active Corannulene Buckybowls in a Crystalline Hybrid Scaffold. (22nd December 2015) - Fellows, W. Brett; Rice, Allison M.; Williams, Derek E.; Dolgopolova, Ekaterina A.; Vannucci, Aaron K.; Pellechia, Perry J.; Smith, Mark D.; Krause, Jeanette A.; Shustova, Natalia B.
Abstract: A porous crystalline corannulene‐containing scaffold, which combines the periodicity, dimensionality, and structural modularity of hybrid frameworks with the intrinsic properties of redox‐active π‐bowls, has been prepared. Single‐crystal and powder X‐ray diffraction, ab initio density functional theory computations, gas sorption analysis, fluorescence spectroscopy, and cyclic voltammetry were employed to study the properties of the novel corannulene derivatives and the buckybowl‐based hybrid materials. X‐ray diffraction studies revealed the preservation of the corannulene bowl inside the prepared rigid matrix, which offers the unique opportunity to extend the scaffold dimensionality through the buckybowl curvature. Merging the inherent properties of hybrid frameworks with the intrinsic properties of π‐bowls opens a new avenue for preparing redox‐active materials and potentially improving charge transport in the scaffold.